Development of Analytical Model for Energy Audit of Refrigeration Systems - Abdul Karim, Z. A.; Yongo A., Philip Waden (2008)
Energy audit and management of refrigeration systems can be manage by analytical models. This paper discuses the analytical model constructed for energy auditing and management of refrigeration systems that currently operate in the gas district cooling plant in Universiti Teknologi PETRONAS (UTP). Mismanagement of energy and energy loses in refrigeration systems can decrease the performance of the systems. The analytical model can be use as a tool for identifying the performance of the refrigeration systems, which consist of the steam absorption chiller, and air cooled chiller. The first law of thermodynamics has been applied for the model construction. After a written script files in a Matlab programming language, sequentially the energy were calculated in the systems, whereby the input and output energy and energy lose in each component were quantified. The operating and design parameters of the systems at their optimum operation were used for model validation.